2011
DOI: 10.1007/s11430-010-4137-2
|View full text |Cite
|
Sign up to set email alerts
|

Upper mantle anisotropy in the Ordos Block and its margins

Abstract: Based on the polarization analysis of teleseismic data, SKS (SKKS) fast-wave directions and delay times between fast and slow shear waves were determined for each of the 111 seismic stations from both permanent and temporary broadband seismograph networks deployed in the Ordos Block and its margins. Both the Silver and Chan and stacking analysis methods were used. In this way, an image of upper mantle anisotropy in the Ordos Block and its margins was acquired. In the western and northern margins of the Ordos B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Zhao et al, 2007;L. Zhao et al, 2007;Liu et al, 2008;Wang et al, 2008;Chang et al, 2009;Bai et al, 2010;Li and Niu, 2010;Chang et al, 2011;Huang et al, 2011;Li et al, 2011;Zhao et al, 2011). We note however that some of these studies obtained fast directions that varied by more than 30°for a given station.…”
Section: Methodsmentioning
confidence: 59%
See 2 more Smart Citations
“…Zhao et al, 2007;L. Zhao et al, 2007;Liu et al, 2008;Wang et al, 2008;Chang et al, 2009;Bai et al, 2010;Li and Niu, 2010;Chang et al, 2011;Huang et al, 2011;Li et al, 2011;Zhao et al, 2011). We note however that some of these studies obtained fast directions that varied by more than 30°for a given station.…”
Section: Methodsmentioning
confidence: 59%
“…This report showed that the uniform fast directions of the anisotropy in eastern China (WNW-ESE) are generally consistent with the absolute plate motion direction of the Eurasian plate, suggesting that the anisotropy is mainly located in the asthenosphere. Regional studies using better seismic station coverage (e.g., Zhao and Zheng, 2005;Liu et al, 2008;Bai et al, 2010;Li and Niu, 2010;Zhao and Xue, 2010;Chang et al, 2011;Li et al, 2011;Zhao et al, 2011) show greater spatial variations in splitting parameters however.…”
Section: Previous Studies On the Upper Mantle Anisotropy Of Eastern Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The Alxa block and the Ordos block, which are traditionally considered to be parts of the western North China Craton (NCC), have resisted the northeastward expansion of the Tibetan Plateau [ Chang et al ., ; Shen et al ., ]. Whether or not these two blocks have been modified is a subject of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Large areas of high-pressure metamorphic rocks (HP) and ultrahigh pressure metamorphic rocks (UHP) have been exposed in the Hong'an and Dabie areas, resulting in a higher degree of research but a lower level in other areas. In addition, many scholars also have great differences and disputes on the existence of the Tibetan Plateau eastward flow channel under the Qinling Mountains orogenic belt (Enkelmann et al, 2006;Chang et al, 2011;He et al, 2015;Zhang et al, 2015;Wang et al, 2016). The main advantage of noise imaging is that it can obtain more short period dispersion data without relying on the location of the source, and the resolution of the shallow crust is greatly improved (Wang and Gao, 2014).…”
Section: Introductionmentioning
confidence: 99%